Sozialmodelle im internationalen Vergleich: wo stehen die neuen EU-Mitgliedstaaten - Michael Knogler; Fidelis Lankes (Osteuropa-Institut Regensburg, 2008)
This paper explores social models in Europe with focus on the new EU Member States in a comparative perspective. The analysis is based on indicators representing the main tasks of social models. Principal components analysis yields three synthetic factors that reflect these tasks: the factor labour market security captures the flexibility and income security on labour markets. It might be interpreted as an indicator of flexicurity which plays a dominant role in the modernization of European social models as envisaged by the Lisbon strategy. Further factors are social equity and personal responsibility; the latter characterizing the trade-off between the usage of welfare transfers and the regulat-ing power of liberal employment protection. These components give rise to five country groups which however only partially coincide with the regional clustering proposed in the literature. Most of the new EU-member states together with Italy and Greece form a group of their own which is characterised by low labour market security and low personal responsibility.
Keywords: 330; Sozialstaat; Systemvergleich; EU-Staaten (Osteuropa); Welt